Linkage analysis of obesity phenotypes in pre- and post-menopausal women from a United States mid-western population - Hilker Christopher A; Wang Alice; Cunningham Julie M; Pankratz V Shane; de Andrade Mariza; Atkinson Elizabeth J; Kelemen Linda E; Couch Fergus J; Sellers Thomas A; Vachon Celine M (BMC, 2010)
Abstract Background Obesity has a strong genetic influence, with some variants showing stronger associations among women than men. Women are also more likely to distribute weight in the abdomen following menopause. We investigated whether genetic loci link with obesity-related phenotypes differently by menopausal status. Methods We performed univariate and bivariate linkage analysis for the phenotypes of body mass index (BMI), waist (W) and hip (H) circumferences (WC, HC), and WH ratio (WHR) separately among 172 pre-menopausal and 405 post-menopausal women from 90 multigenerational families using a genome scan with 403 microsatellite markers. Bivariate analysis used pair-wise combinations of obesity phenotypes to detect linkage at loci with pleiotropic effects for genetically correlated traits. BMI was adjusted in models of WC, HC and WHR. Results Pre-menopausal women, compared to post-menopausal women, had higher heritability for BMI (h2 = 94% versus h2 = 39%, respectively) and for HC (h2 = 99% versus h2 = 43%, respectively), and lower heritability for WC (h2 = 29% versus h2 = 61%, respectively) and for WHR (h2 = 39% versus h2 = 57%, respectively). Among pre-menopausal women, the strongest evidence for linkage was for the combination of BMI and HC traits at 3p26 (bivariate LOD = 3.65) and at 13q13-q14 (bivariate LOD = 3.59). Among post-menopausal women, the highest level of evidence for genetic linkage was for HC at 4p15.3 (univariate LOD = 2.70) and 14q13 (univariate LOD = 2.51). WC was not clearly linked to any locus. Conclusions These results support a genetic basis for fat deposition that differs by menopausal status, and suggest that the same loci encode genes that influence general obesity (BMI) and HC, specifically, among pre-menopausal women. However, lower heritability among pre-menopausal women for WC and WHR suggests that pre-menopausal waist girth may be influenced to a greater extent by controllable environmental factors than post-menopausal waist girth. Possibly, targeted interventions for weight control among pre-menopausal women may prevent or attenuate post-menopausal abdominal weight deposition.